Effect of Irrigation and Mulching on Growth and Yield of Ginger (Bangladesh Agronomy Journal, 2015)
A field experiment was conducted at the Spices Research Center, BARI, Bogra, Bangladesh during 2009-10 to determine the impact of irrigation and suitability of mulch materials on the growth and yield of ginger. The experiment was laid out in the randomized complete block design (RCBD) with three replications. The treatments comprising of two factors viz., two irrigation (I1: irrigation in dry period and I2: control i.e. no irrigation and three mulching material (M0: control (no mulch) M1: water hyacinth and M2: rice straw). Treatment revealed that I1: (irrigation in dry period) showed that early emergence, highest plant height, number of leaves/plant, number of tillers/plant with maximum weight of primary and secondary rhizome, highest dry matter % and weight of old mother rhizome t ha-1. The highest yield of rhizome (21.19 t ha-1) was obtained from I1: (irrigation in dry period). Among the mulch treatments, the highest rhizome yield (22.51 t ha-1) was obtained from M2 (ricer straw mulch). The combined effect of I1M2 (irrigation in dry period with rice straw mulch) produced the highest rhizome yield (25.07 t ha-1).Bangladesh Agron. J. 2015, 18(1): 27-36